2012
DOI: 10.4236/ojvm.2012.22007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase-2 and Ki-67 in Actinic Keratosis and Cutaneous Squamous Cell Carcinoma in Dogs

Abstract: Actinic keratosis is a common disease in humans, which also affects dogs. Lesions occur in chronically sun exposed areas, such as flank, ventral and lateral abdomen. It has been reported that actinic keratosis is a pre-neoplastic disease which may evolve into squamous cell carcinoma (SCC), which is one of the most frequent malignant neoplasm in dogs. The aim of this research was to investigate the relationship between COX-2 and cell proliferation on the outcome of dogs with actinic keratosis and cutaneous squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
3
11
0
1
Order By: Relevance
“…Because ECT is a recent technique in Veterinary Medicine, a limited number of studies have demonstrated the ECT antitumoral effect in cSCC. In general, the high expression level of Ki67 observed in SCC, especially in poorly differentiated SCC, is related to an aggressive potential [9,34,37,49]. However, in the lesions studied, the proliferation index could also be considered high despite the predominance of well-differentiated SCC (83.3%), suggesting the aggressive potential, despite the degree of differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ECT is a recent technique in Veterinary Medicine, a limited number of studies have demonstrated the ECT antitumoral effect in cSCC. In general, the high expression level of Ki67 observed in SCC, especially in poorly differentiated SCC, is related to an aggressive potential [9,34,37,49]. However, in the lesions studied, the proliferation index could also be considered high despite the predominance of well-differentiated SCC (83.3%), suggesting the aggressive potential, despite the degree of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…cSCC is the second most common cutaneous tumor in dogs [5], with an incidence between 3-20% [6,7]; however, the incidence of cSCC depends on the geographic area [5]. In humans and dogs, actinic keratosis is an SCC precursor lesion with more than 80% of the SCC cases in humans being derived from previous actinic keratosis [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Poor owner compliance with respect to the use of protective sun solar suits before and during the study period would encourage the use of firocoxib as a chemopreventive in solar dermatitis. The rationale for the use of firocoxib in this study is related to the recent demonstration of COX‐2 expression in dogs and cats with squamous cell carcinoma and actinic keratosis . Skin biopsies pretreatment in all five dogs showed COX‐2 immunostaining in the keratinocytes and served as comparison for the assessment of immunostaining in the same dogs during and after firocoxib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of arachidonic acid into prostaglandin is catalysed by the cyclo‐oxygenases (COX); human and laboratory animal studies indicate that COX‐2 is overexpressed in actinic keratosis and squamous cell carcinoma . More recently, COX‐2 expression has been shown in canine and feline actinic keratosis and squamous cell carcinoma …”
Section: Introductionmentioning
confidence: 99%
“…Em nosso estudo, a raça mais acometida foi a American PitBull Terrier, condizendo com a literatura (North;Banks, 2009;Costa, 2009;Vail;Withrow, 2007;Poggiani et al, 2012). As regiões anatômicas mais acometidas pela doença são locais com menor cobertura de pelos, como face interna de membros, plano nasal, pina de orelhas e abdome como descrito em nosso estudo (Almeida et al, 2001, Carvalho, 2008Milanta et al, 2016).…”
Section: Análise Estatísticaunclassified